2001
DOI: 10.1590/s0037-86822001000400015
|View full text |Cite
|
Sign up to set email alerts
|

Low sensitivity of polymerase chain reaction for diagnosis of tuberculous meningitis in southeastern Brazil

Abstract: Two polymerase chain reaction (PCR) protocols showed low sensitivity (36% and 53% for TB AMPLICOR and MPB64 nested PCR, respectively), when compared with classic microbiological methods (73% and 54% for Ziehl-Neelsen staining and culture, respectively), in the diagnosis of tuberculous meningitis in 91 patients in southeastern Brazil. Only three PCR-positive, microbiologically negative patients were found. Analysis of sequential cerebrospinal fluid samples by nested PCR detected Mycobacterium tuberculosis DNA u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
1
13
1
5
Order By: Relevance
“…AP staining, though it has been claimed to be more sensitive than the ZN staining [15], in the present study, we could notice no significant differences. The sensitivity of the culture on the LJ medium (3.22%) was similar to that which was found in various other studies (2-8%) [13][14] . This could be due to the pacibacillary nature of the CSF (the minimum detection threshold being 10-100 bacilli per ml) or due to the presence of dead bacilli [8].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…AP staining, though it has been claimed to be more sensitive than the ZN staining [15], in the present study, we could notice no significant differences. The sensitivity of the culture on the LJ medium (3.22%) was similar to that which was found in various other studies (2-8%) [13][14] . This could be due to the pacibacillary nature of the CSF (the minimum detection threshold being 10-100 bacilli per ml) or due to the presence of dead bacilli [8].…”
Section: Discussionsupporting
confidence: 89%
“…A high bacterial load (>10 4 -10 5 bacilli/ml) is needed in the specimen, to render an AFB microscopy result positive [5]. Various studies documented similar sensitivities of the smear microscopy for TBM, which ranged from 0-20% [2,[13][14]. AP staining, though it has been claimed to be more sensitive than the ZN staining [15], in the present study, we could notice no significant differences.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…These assays have been evaluated specifically in HIV-coinfected patients (59,180) and also as a means to monitor therapy (180,210). While many of those studies demonstrated improved sensitivity over traditional smear and culture methods, several other studies highlighted the low sensitivities associated with these PCR assays (25,68,112,164,206). Looking at the utility of applying PCR assays to the (206).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%
“…El rendimiento diagnóstico de IgM anti-A60 (sensibilidad de 94,1% y especificidad de 80,4%) resultó incluso superior a lo reportado en numerosos estudios para la RPC de M. tuberculosis en LCR 3,6,23 . Este hallazgo pudiese explicarse por la gran antigenicidad de M. tuberculosis que resulta en la producción de anticuerpos detectables mediante ELISA pese a que la carga misma de antígenos micobacterianos sea muy baja en la muestra de LCR 8,24 .…”
Section: Discussionunclassified